2016
DOI: 10.1590/1980-5373-mr-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Al-TON Zeolite Using a Dialkylimizadolium as Structure-Directing Agent

Abstract: In this work, the synthesis of zeolites using 1-butyl-3-methylimidazolium chloride [C 4 MI]Cl as a structure-directing agent was investigated. The organic cation shows effectiveness and selectivity for the syntheses of TON zeolites under different reaction conditions compared to the traditional structuredirecting agent, 1,8-diaminooctane. The 1-butyl-3-methylimidazolium cation lead to highly crystalline materials and its role as OSDA in our synthesis conditions has been confirmed by characterization technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…The observed diffraction angles were in good agreement with previous reports, thereby confirming the crystalline state of the aluminosilicates. As reported earlier, three notable diffraction peaks in the range of 15 to 35 degrees indicated the face-centered spherical crystalline index of the aluminoslicate 35,36 . However, the diffraction lines of (100) and indicated lattice fringes that correspond to the planes of a cubic structure 37 .…”
Section: X-ray Diffraction Spectroscopy (Xrd) Aluminosilicate Nanocosupporting
confidence: 73%
“…The observed diffraction angles were in good agreement with previous reports, thereby confirming the crystalline state of the aluminosilicates. As reported earlier, three notable diffraction peaks in the range of 15 to 35 degrees indicated the face-centered spherical crystalline index of the aluminoslicate 35,36 . However, the diffraction lines of (100) and indicated lattice fringes that correspond to the planes of a cubic structure 37 .…”
Section: X-ray Diffraction Spectroscopy (Xrd) Aluminosilicate Nanocosupporting
confidence: 73%
“…Recently, Wen et al [19] noted that the size of 1butyl-3-methylimidazolium (one of the most investigated ionic liquids found in literature [30,31]) is consistent with the channel size of TON, what makes it a good candidate as structure-directing agent for this topology. Indeed, this behavior was confirmed by our group in the synthesis of TiO 2 and Al-containing TON zeolite in hydroxide media [10,11].…”
Section: Introductionsupporting
confidence: 60%
“…Using a similar procedure, the synthesis of Al-containing ZSM-22 was studied by adding aluminum salt to the starting gel. Lopes et al (2016) reported the synthesis of the Al-TON structure using 1-butyl-3-methylimidazolium chloride as OSDA. This organic cation showed greater efficiency and selectivity for the synthesis of TON zeolites under different reaction conditions compared to 1,8-diaminooctane (a traditional OSDA).…”
Section: Introductionmentioning
confidence: 99%